Evidence Basis for Regional Anesthesia in Ambulatory Anterior Cruciate Ligament Reconstruction: Part III. (March 2019) - Yung, Eric M.; Brull, Richard; Albrecht, Eric; Joshi, Girish P.; Abdallah, Faraj W.
Abstract : BACKGROUND: Local infiltration analgesia offers effective postoperative analgesia after knee arthroplasty, but the role of its counterpart, local instillation analgesia (LIA), in anterior cruciate ligament reconstruction (ACLR) is unclear. This systematic review and meta-analysis evaluates the analgesic benefits of LIA for outpatient ACLR. METHODS: We sought randomized controlled trials investigating the analgesic effects of LIA versus control in adults having outpatient ACLR and receiving multimodal analgesia (excluding nerve blocks, which are examined in parts I and II of this project). Cumulative postoperative analgesic consumption at 24 hours was designated as a primary outcome. Analgesic consumption during postanesthesia care unit stay, proportion of patients requiring analgesic supplementation, time-to-first analgesic request, rest pain scores during the first 48 hours, hospital length of stay, and incidence of opioid-related side effects were analyzed as secondary outcomes and pooled using random effects modeling. RESULTS: Eleven randomized controlled trials (515 patients) were included. Analgesic consumption was selected as the primary outcome in 4 trials (36%). Compared to control, LIA reduced the 24-hour morphine consumption by a weighted mean difference (95% confidence interval) of −18.0 mg (−33.4 to −2.6) ( P = .02). LIA reduced postanesthesia care unit morphine consumption by −55.9 mg (−88.4 to −23.4) ( P < .05) and decreased the odds (odds ratio [95% confidence interval]) of analgesic supplementation during the first 24 hours by 0.4 (0.2–0.8) ( P = .004). LIA also improved pain scores during the 0–24-hour interval, most notably at 4 hours (−1.6 [−2.2 to −1.0) ( P < .00001). CONCLUSIONS: Administering LIA for outpatient ACLR improves postoperative analgesia by decreasing opioid consumption and improving pain control up to 24 hours, with minimal complications. These findings encourage integrating LIA into the care standard for ACLR. Questions regarding the ideal LIA components, location, and role in the setting of hamstring grafts require further research.